EKSPLORASI TUMBUHAN BERPOTENSI DERMATOFITOSIS DI KECAMATAN SINDANG BELITI ILIR KABUPATEN REJANG LEBONG - Titin Sumarni; Destien Atmi Arisandy; Linna Fitriani (Yayasan Nusantara Hasana Berdikari, 2024)
This study aims to explore the types of plants that have the potential for dermatophytosis, the parts of plants that have the potential for dermatophytosis that are used, the method of processing plants that have the potential for dermatophytosis, abiotic factors in Sindang Beliti Ilir District, Rejang Lebong Regency. Pure research methods used are observation and interviews and development research using the Borg and Gall model. Data collection techniques using observation techniques, interviews and documentation. The research samples were in 6 villages including Lubuk Belimbing I Village, Lubuk Belimbing II Village, Lubuk Bingin Baru Village, Periang Village, Suka Merindu Village, and Sari Pulau Village. Research Results Exploration of plants, there are 8 families namely fabaceae, myrtaceae, zigiberaceae, piperaceae, caricsceae, poaceae, asphodelaceae, palmae and 13 species. The parts of the plant used were 7% roots, 27% rhizomes, 53% leaves, 7% flowers and 6% fruit. The percentage used for processing plants with the potential for Dermatophytosis is boiling 23%, smearing 69%, and consuming 8%.